Effective daylight design strategies of colonial mosques in Malaysia - Sanusi, Aliyah Nur Zafirah; Abdul Jamil, Ahmad Faisal; Abdullah, Fadzidah; Othman, Rosniza (e-IPH Ltd UK., 2021)
This study evaluates the effective Daylighting design strategies of Colonial Mosques in Malaysia. There are two objectives, and the first objective is to examine the Daylighting performance of the main prayer hall of three Colonial Mosques in Malaysia. The second objective is to identify effective Daylighting design strategies from the Colonial Mosques in Malaysia. The triangular research methodology was applied for this study. The research methodology consists of literature review, field observation, and Daylighting analysis simulation with Sefaira simulation software. In conclusion, window heights influence the Daylighting performance of the main prayer hall. Higher windows give more effective Daylighting.